Isolation of 15 new polymorphic microsatellite markers from the blue-spine unicornfish Naso unicornis - Horne, J.; McIlwain, Jennifer; van Herwerden, L. (Springer, 2010)
The blue-spine unicornfish Naso unicornis is a widely distributed reef herbivore that is highly prized in tropical Indo-Pacific fisheries. Appropriate management for N. unicornis and other exploited reef fishes requires detailed knowledge of larval migrant exchange between isolated adult meta-populations and an understanding of recruitment patterns at both local and larger geographic scales. To this end, we have developed 15 microsatellite loci to evaluate levels larval connectivity and detect genetic patterns relevant to demographic processes in this species. Microsatellites were isolated from total genomic DNA using biotinylated probes and magnetic bead capture. We screened these loci against 90 individuals sampled from Guam in the tropical West Pacific. Loci contained 5–23 alleles (mean = 15.7) and had a mean observed and expected heterozygosity of 0.66 and 0.82, respectively. One locus, which did not conform to the expectations of Hardy–Weinberg equilibrium, is probably under selection. Four others are probably confounded by the presence of null alleles.